2007
DOI: 10.1063/1.2434799
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of free-surface breakup in vibration-induced liquid atomization

Abstract: The mechanisms of droplet formation that take place during vibration-induced drop atomization are investigated experimentally. Droplet ejection results from the breakup of transient liquid spikes that form following the localized collapse of free-surface waves. Breakup typically begins with capillary pinch-off of a droplet from the tip of the spike and can be followed by additional pinch-offs of satellite droplets if the corresponding capillary number is sufficiently small (e.g., in low-viscosity liquids). If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…It is well known that the energy generated from an ultrasonic transducer covered by a liquid film results in the formation of capillary waves on the liquid surface and ejection of droplets from the surface, a process which is called ultrasonic atomization. 6 This simply indicates that the energy of vibration can significantly agitate the impinged droplets, thus improving mixing, spreading, and wetting. When individual droplets, such as sessile droplets placed on a substrates, are considered, it has been shown that vibrating or shaking the droplets or the substrate results in unpinning and moving of the droplet contact line and a change in the contact angle; thus, droplet spreading may enhance and droplets may even move uphill.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that the energy generated from an ultrasonic transducer covered by a liquid film results in the formation of capillary waves on the liquid surface and ejection of droplets from the surface, a process which is called ultrasonic atomization. 6 This simply indicates that the energy of vibration can significantly agitate the impinged droplets, thus improving mixing, spreading, and wetting. When individual droplets, such as sessile droplets placed on a substrates, are considered, it has been shown that vibrating or shaking the droplets or the substrate results in unpinning and moving of the droplet contact line and a change in the contact angle; thus, droplet spreading may enhance and droplets may even move uphill.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, James et al 5 utilized a low-frequency vibration to study droplet ejection numerically, and elucidated that droplet ejection was due to a pinch-off phenomenon involving detachment from a main drop that was initially positioned on the surface of the vibrating solid wall. Vibration-induced drop atomization has also been investigated by Vukasinovic et al, 6 while Yule and Al-Suleimani 7 have studied the formation of fine droplets due to the collapse of capillary waves produced by surface vibration of shallow water.…”
Section: Introductionmentioning
confidence: 98%
“…James et al (2003), in the formation of a simple mathematical model, explored the nonlinearity of the phenomena at very low frequencies and considered qualitative aspects of the process absent from other papers. A subsequent work by Vukasinovic et al (2007b) focused specifically on the mechanism of breakup to form single ejected drops and large numbers of drops, which appear under different excitation conditions, and the lengths of jets that form from the capillary wave. Their results are similar to Goodridge et al (1997) for the transition to atomization, although they also found, for cases where the drop ejection does not directly depend upon the viscosity (i.e., the capillary number Ca ( 1), that the threshold acceleration depends only on a nondimensional drop size that is essentially the same as Eq.…”
Section: =3mentioning
confidence: 99%